2008
DOI: 10.1007/s00280-008-0881-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the tumor microenvironment: a review of an essential relationship

Abstract: Purpose-The role of the microenvironment during the initiation and progression of carcinogenesis is now realized to be of critical importance, both for enhanced understanding of fundamental cancer biology, as well as exploiting this source of relatively new knowledge for improved molecular diagnostics and therapeutics.Methods-This review focuses on: (1) the approaches of preparing and analyzing secreted proteins, (2) the contribution of tumor microenvironment elements in cancer, and (3) the potential molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
319
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(326 citation statements)
references
References 95 publications
1
319
0
6
Order By: Relevance
“…Efforts to address this issue led to the sequence alignment between tTG and Human factor XIIIA, a hetero-tetrameric transglutaminase-family member implicated in blood coagulation (46). The X-ray crystal structure of the human recombinant, dimeric fXIIIA2 was determined in 1994 (47), and sequence homology between XIIIA and tTG predicted that tTG probably folded into four sequential domains: an N-terminal -sandwich domain, the central catalytic core domain, and two -barrel domains at the C-terminal end of this protein (48). This result was confirmed by the first tTG structure that was solved in 2002 at 2.8 Å resolution, which…”
Section: A Comparison Between the Active And Inactive Conformation Ofmentioning
confidence: 99%
“…Efforts to address this issue led to the sequence alignment between tTG and Human factor XIIIA, a hetero-tetrameric transglutaminase-family member implicated in blood coagulation (46). The X-ray crystal structure of the human recombinant, dimeric fXIIIA2 was determined in 1994 (47), and sequence homology between XIIIA and tTG predicted that tTG probably folded into four sequential domains: an N-terminal -sandwich domain, the central catalytic core domain, and two -barrel domains at the C-terminal end of this protein (48). This result was confirmed by the first tTG structure that was solved in 2002 at 2.8 Å resolution, which…”
Section: A Comparison Between the Active And Inactive Conformation Ofmentioning
confidence: 99%
“…Both inflammatory and stromal cells are important for tumor progression. 2,3 In cervical carcinoma there is a high amount of inflammatory infiltrate, and we have recently shown a correlation between a high number of intraepithelial regulatory T cells (Treg) and poor survival of cervical carcinoma patients. 4 Stromal cells produce growth factors and extracellular matrix (ECM) components and provide an adequate environment for angiogenesis.…”
mentioning
confidence: 99%
“…However, several studies have indicated that tumor pathogenesis and progression are closely associated with the tumor microenvironment, as well as tumor cells themselves (13). Recent studies have suggested that a systemic inflammatory state is associated with the malignant biological behavior of the tumor (14,15).…”
Section: Introductionmentioning
confidence: 99%